Peningkatan Kemampuan Berpikir Kritis dan Hasil Belajar IPA Menggunakan Model Problem Based Learning Siswa Kelas V SDN Kropak - Sulistyawati, Puput (Tuladha : Jurnal Pendidikan Dasar, 2025)
Abstract: The background of this study is the low critical thinking skills and learning outcomes of students in science learning at SDN Kropak. This study aims to: improve critical thinking skills and learning outcomes of fifth grade students in science subjects through the application of the Problem based learning (PBL) learning model. This type of research is classroom action research. The subjects of this study were fifth grade students of SDN Kropak. The object of the study was improving critical thinking attitudes and science learning outcomes of students using the Problem based learning (PBL) learning model. This study used data collection techniques in the form of observation, interviews and tests. The results of this study indicate that (1) the Problem based learning (PBL) learning model can improve students' critical thinking skills, indicated by the average score of critical thinking skills in cycle I, which was 64.18 to 80.38 in cycle II. (2) the Problem based learning (PBL) learning model can improve students' learning outcomes from an average initial condition value of 69.3 increasing to 76.21 in cycle I and increasing again in cycle II, which was 82.19.